Reuse locality aware cache partitioning for last-level cache. (March 2019) - Shen, Fanfan; He, Yanxiang; Zhang, Jun; Li, Qingan; Li, Jianhua; Xu, Chao
Abstract: Cache partitioning is a promising technique to improve cache management mechanism. To explore the advantages of cache partitioning, most existing schemes either consider performance improvement or address energy reduction. These techniques focus on specific application domain or single optimization goal, which limit their extensive use. To address these issues, this paper proposesR euse lO cality awareC ache pA rtitioning scheme (ROCA) to reserve more high reuse locality blocks in the last level cache. ROCA uses a reuse locality reservation algorithm to maintain the cache fraction. Meanwhile, reuse locality guided block placement policy is proposed to further improve cache efficiency. Evaluation results show that the proposed technique improves energy efficiency as well as system performance with reduced hardware cost, compared to the state-of-the-art approach.